2014
DOI: 10.5194/tc-8-195-2014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of uncertainty in surface mass balance–elevation feedback on projections of the future sea level contribution of the Greenland ice sheet

Abstract: Abstract. We apply a new parameterisation of the Greenland ice sheet (GrIS) feedback between surface mass balance (SMB: the sum of surface accumulation and surface ablation) and surface elevation in the MAR regional climate model (Edwards et al., 2014) to projections of future climate change using five ice sheet models (ISMs). The MAR (Modèle Atmosphérique Régional: Fettweis, 2007) climate projections are for 2000-2199, forced by the ECHAM5 and HadCM3 global climate models (GCMs) under the SRES A1B emissions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(138 citation statements)
references
References 44 publications
5
133
0
Order By: Relevance
“…Based on climate projections under the A1B scenario used to force five ice sheet models, Edwards et al [103] found that the SMBelevation feedback accounts for an additional 1.8-6.9 % (95 % confidence interval) sea level rise by 2100, in agreement with the AR5.…”
Section: Greenland Ice Sheetmentioning
confidence: 63%
“…Based on climate projections under the A1B scenario used to force five ice sheet models, Edwards et al [103] found that the SMBelevation feedback accounts for an additional 1.8-6.9 % (95 % confidence interval) sea level rise by 2100, in agreement with the AR5.…”
Section: Greenland Ice Sheetmentioning
confidence: 63%
“…In addition, SIA/ SSA ISMs satisfactorily simulate present-day and future GIS conditions compared with more complex ISMs (e.g. Edwards and others, 2014). For example, in the case of the main drainage areas, such as the NEGIS, SIA, hybrids, higher-order and full-Stokes all fail to accurately reproduce the observations (e.g.…”
Section: Hybrid Model Limitationsmentioning
confidence: 99%
“…This methodology slightly reduces the modeldata agreement achievable when using fixed surface and inverse methods together (e.g. Edwards and others, 2014;Lee and others, 2015), but it provides a more realistic temperature profile. Consequently, an unique technique to properly initialize ISMs has not yet been found (e.g.…”
Section: Ice-sheet Initializationmentioning
confidence: 99%
See 2 more Smart Citations